Criminal Verdicts Under the Special Minimum in Regional Head Elections: A Perspective of Justice - Priyadi, M. Herris; Saripudin, Iip (Intellectual Law Review (ILRE), 2024)
The purpose of this research is to examine criminal judgements made below the specific minimum threshold in regional head election cases that pose a dilemma between justice and legal certainty. This research uses secondary data collected from literature study; normative juridical method and descriptive analysis are used. The results show that the objectives of punishment are affected by verdicts below the specific minimum, especially in terms of public order and the integrity of the democratic process. Although this may override the principle of legal certainty, judges usually prioritise a sense of justice by considering the defendant's mitigating factors. In summary, a clearer revision of the regulations should be included with the penal policy and its implementation. This will help judges balance substantive justice and legal certainty.